Strategi Pemerintah Dalam Pembangunan Infrastruktur Jalan Di Kabupaten Gowa - Kasmira, Kasmira; Alyas, Alyas; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This is study purposed to find out the government’s strategy in the construction of road infrastructure in Gowa Regency. This study used qualitative descriptive study, while data collection techniques used observation, interviews and documentation. This study consisted of 5 informants were head of Highways, Section for Road Development/Improvement, Road and Bridge Maintenance Section, and 2 people/road users. Data Sources used primary and secondary data, data analysis techniques with data reduction, data presentation and verification. The data validation used source triangulation, technique triangulation, and time triangulation. The result of this study showed thhat the government Strategy in the development of Road Infrastructure in Gowa Regency had been run well because in terms of human resources, effectiveness, objectives were maximally appropriate without waste (not wasting time, energy, cost) able to carry out tasks correctly and accurately. Although it had not run optimally due to constraint that often accured, namely the delayed budget/cost, so the implementation of road construction or maintenance was still less efficient.